Pengalaman Ibu Merawat Anak dengan Tunagrahita di Bandar Lampung - Marliyana Marliyana (Jurnal Kesehatan, 2017)
Mental retardation is a condition that intelegency has significant below average and accompanied by incompetence in the adaptation behavior that appeared in the development. Sometimes, parents who has a mental retardation children didn’t concern with their growth and developments factors. This study was to explore the mother’s experiences in caring for children with mental retardation in Bandar Lampung. It was the qualitative study with the phenomenology approach. Respondent were the mother who has children with mental retardation, total number were 6 peoples. Data were collected by indepth interview. Data were analyzed using thematic analysis according to Collaizz methode. The results showed that there were six theme: 1) mother’s Response who has a mental retardation children, 2) caring a mental retardation children, 3) family’s treatment in caring for a children mental retardation, 4) kinds of family support, 5) spiritual message to family who has mental retardation children, 6) family’s hope who has a mental retardation children.